The role of high-, moderate-, and low-intensity training in enhancing functional mobility and muscle strength of aged female: a randomized controlled trial - Ghasemabad, Kamran Hosseinzadeh; Tengku Kamalden, Tengku Fadilah; Omar Dev, Roxana Dev; Nekooei, Pooya; Majlesi, Sara; Alemi, Behzad; Nekouei, Paria (Universiti Putra Malaysia Press, 2022)
Resistance training provides many benefits to the older population, and it is considered one of the most effective ways to counter-attack age-related sarcopenia and dynapenia disorders. This article evaluates the impacts of high, moderate, and low training intensities on muscle strength and functional mobility of older adults. A single-blinded factorial design for 12 weeks was conducted among 60 healthy older Malaysian women (>65 years). The authors assessed the Five times Sit to Stand (5STS), the Timed Up and Go test (TUG), and the 6 Minutes Walking Test (6MWT). The participants were randomly divided to the HighIntensity Group (HIT; n=15) (69.60 ± 3.68); Moderate-Intensity Group (MIT; n=15) (69.27 ± 3.41); Low-Intensity Training (LIT; n=15) (69.27 ± 1.94); and Control Group (CG; n=15) (68.67 ± 2.38). In terms of time, there is a statistically noticeable difference in the means of all the variables (p< .001). Moreover, a statistically significant connection between the intervention and time was seen on all the variables (p< .001). However, there was a statistically significant difference between the means of 5STS (P< .001) and TUG (P= .025) in the intervention groups, there was no statistically significant difference observed in 6MWT (P= .90). The results suggested that all of these intensities training are beneficial for improving muscle strength and functional mobility. In addition, the HIT is more effective in improving the 5STS, TUG, and 6MWT, as compared to the MIT, LIT, and CG. These findings revealed that HIT tends to result in greater improvement of muscle strength and mobility.